The syndicate. Series 1 [videorecording (DVD)] - Spall, Timothy, 1957-; Page, Joanna, 1978-; McNulty, Matthew, 1982- (Acorn Media, 2013)
Five poor workers in a supermarket in Leeds whose lives turn upside down after they jointly win the lottery.